Self-Reported Stickiness of Mind-Wandering Affects Task Performance - van Vugt, Marieke K.; Broers, Nico (Frontiers in Psychology, 2016)
When asked to perform a certain task, we typically spend a decent amount of time thinking thoughts unrelated to that task--a phenomenon referred to as 'mind-wandering.' It is thought that this mind-wandering is driven at least in part by our unfinished goals and concerns. Previous studies have shown that just after presenting a participant with their own concerns, their reports of task-unrelated thinking increased somewhat. However, effects of these concerns on task performance were somewhat inconsistent. In this study we take the opposite approach, and examine whether task performance depends on the self-reported thought content. Specifically, a particularly intriguing aspect of mind-wandering that has hitherto received little attention is the difficulty of disengaging from it, in other words, the ''stickiness'' of the thoughts. While presenting participants with their own concerns was not associated with clear effects on task performance, we showed that the reports of off-task thinking and variability of response times increased with the amount of self-reported stickiness of thoughts. This suggests that the stickiness of mind-wandering is a relevant variable, and participants are able to meaningfully report on it.